2018
DOI: 10.1002/cncr.31298
|View full text |Cite
|
Sign up to set email alerts
|

High control rates of proton‐ and carbon‐ion–beam treatment with intensity‐modulated active raster scanning in 101 patients with skull base chondrosarcoma at the Heidelberg Ion Beam Therapy Center

Abstract: No significant difference between carbon ions and protons in the therapy of skull base chondrosarcoma could be detected in these initial retrospective results. Cancer 2018;124:2036-44. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 29 publications
2
40
1
Order By: Relevance
“…In support of the hypothesis of dose homogeneity and HSV coverage driving improved LC, it has been shown that there are no significant differences in LC between doses greater than and doses less than or equal to 85 BED 10 , GyRBE . Furthermore, a modern trial using protons with a median dose of 70 Gy to treat chondrosarcoma at the Heidelberg Ion Beam Therapy Center found 4‐year OS and LC rates of 100% with modern techniques in particle therapy, albeit only for 22 patients . These findings are important because further dose escalation may have only a limited benefit as the prescribed dose has not been predictive of LC in a large experience .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In support of the hypothesis of dose homogeneity and HSV coverage driving improved LC, it has been shown that there are no significant differences in LC between doses greater than and doses less than or equal to 85 BED 10 , GyRBE . Furthermore, a modern trial using protons with a median dose of 70 Gy to treat chondrosarcoma at the Heidelberg Ion Beam Therapy Center found 4‐year OS and LC rates of 100% with modern techniques in particle therapy, albeit only for 22 patients . These findings are important because further dose escalation may have only a limited benefit as the prescribed dose has not been predictive of LC in a large experience .…”
Section: Discussionmentioning
confidence: 94%
“…29 Furthermore, a modern trial using protons with a median dose of 70 Gy to treat chondrosarcoma at the Heidelberg Ion Beam Therapy Center found 4-year OS and LC rates of 100% with modern techniques in particle therapy, albeit only for 22 patients. 30 These findings are important because further dose escalation may have only a limited benefit as the prescribed dose has not been predictive of LC in a large experience. 27 Because the treatment field size tends to inversely correlate with dose homogeneity, other prognostic factors such as a GTV < 25 cc 13,17,31 and a planning target volume ≤ 70 cc 29 have been associated with improved LC, and this helps to emphasize the importance of gross total resection before PRT.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, PBRT for head and neck sarcomas, including those involving skull base, produced effective tumor controls, and overall survivals in both primary and recurrent patients; the 1/2-year OS and LRFS for the entire cohort were 92.9/90.0 and 88.4/78.9%, respectively (24,25). For chondrosarcoma of the skull base, PBRT attained more favorable outcomes; results from Heidelberg Ion Beam Therapy Center reported both the 5-year OS, and local controls were over 90% and over 85%, respectively (26,28). Most of the other papers included substantial cases of chordoma of the cervical spine or skull base, a condition that has a significantly different biological behavior from bone and soft-tissue sarcomas (18,26,27).…”
Section: Discussionmentioning
confidence: 98%
“…Also, particle beams with higher linear energy transfer (e.g., carbon ion) produces significantly higher biological effectiveness as compared with photon beams (23), a clear advantage for radioresistant histologies such as most subtypes of sarcomas. Clinical data from several retrospective studies showed that PBRT could achieve favorable disease control for head and neck sarcomas or base of skull tumors, including chordoma and chondrosarcoma, even in patients with unresected or recurrent diseases (24)(25)(26)(27)(28)(29). In our previous studies, PBRT for head and neck sarcomas, including those involving skull base, produced effective tumor controls, and overall survivals in both primary and recurrent patients; the 1/2-year OS and LRFS for the entire cohort were 92.9/90.0 and 88.4/78.9%, respectively (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent publication suggests that equivalent control rates and outcomes were achieved by 101 patients with skull-based chondrosarcomas who received either protons or carbon ions using intensity-modulated, active raster scanning. 22 Furthermore, the published evidence for long-term late effects from these and other therapies is sparse. There is the potential for considerable variability in the RBE of CIRT used clinically and, to a lesser degree, of protons, depending on the biologic models, treatment planning protocols, and treatment volumes currently in use.…”
Section: Introductionmentioning
confidence: 99%